Washington State Building, San Francisco, 1915
Note On verso: Washington State Building Motion Picture Program (with Lectures) 1:00 P.M. Dairying and other Scenes of Washington.H.J. Thomas1:20 P.M. From the raw land to the big red apple and general farming scenes.H.J. Thomas 1:45 P.M. The big tree, from the felling to the finished product of the mill.H.J. Thomas 2:10 P.M. Train-Automobile Race "Four Hours from Tacoma to the Glaciers in Rainier National Park." H.J. Thomas 3:00 P. M. State Educational Institutions.H.J. Thomas 3:20 P.M.Life of the salmon, from the egg to the can.H.J. Thomas 3:40 P.M. Spokane, the power city, "Hub of 'The Inland Empire.'" W.G. Hannam 4:00 P.M. Seattle, "The Metropolis of the Great Northwest" .D.B. Duncombe 4:30 P.M.WashingtonScenic and Industrial.H.J. Thomas